2005
DOI: 10.1016/j.otohns.2005.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric Patterns and Prognosis in Sudden Sensorineural Hearing Loss in Southern Taiwan

Abstract: SSNHL patients with midtone loss have the best prognosis. This study of the audiometric patterns and prognostic factors of SSNHL allow us to better predict its outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
4
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 16 publications
12
89
4
3
Order By: Relevance
“…In our study (as reported by many other Authors) 18,20,[22][23][24][27][28][29]31 with the exception of Lissens et al 32 the presence of objective vertigo (which indicates complex damage to the inner ear) must be considered as a negative prognostic factor of hearing recovery. Therefore, the importance of initial record-taking cannot be sufficiently stressed in terms of its prognostic value.…”
Section: Vertigosupporting
confidence: 63%
See 1 more Smart Citation
“…In our study (as reported by many other Authors) 18,20,[22][23][24][27][28][29]31 with the exception of Lissens et al 32 the presence of objective vertigo (which indicates complex damage to the inner ear) must be considered as a negative prognostic factor of hearing recovery. Therefore, the importance of initial record-taking cannot be sufficiently stressed in terms of its prognostic value.…”
Section: Vertigosupporting
confidence: 63%
“…25,26 As stated in other studies 10,17,22,23,27 sudden hypoacusis requires hospitalization and medical treatment as soon as possible. 28,29 In contrast, Massen et al 30 observed improvements in hearing even when the beginning of the treatment was delayed, and Baujat et al 20 stated that sudden hypoacusis is a false medical emergency because the results are disappointing even when treatment is prompt.…”
Section: Time Since Onsetmentioning
confidence: 91%
“…The negative prognostic effect of profound or total hearing loss is almost agreed worldwide. However, in the literature, there are certain studies which report poor prognosis with flat type or low frequency losses which is an inconsistent finding with the majority of the rest (18,25). This might be attributable, to a certain point, to various classification patterns or diverse treatment modalities utilized by different authors.…”
Section: Discussionmentioning
confidence: 97%
“…More importantly, older age (>60 years) was shown to have a negative prognostic impact with 55.9% of the cases in this age group having no recovery (p=0.046). Although some previous reports have shown that older age is related to negative prognosis [17] , others have found no correlation between age and prognosis [16,18,19] . By contrast, younger patients were reported to have a better prognosis by some authors [20] .…”
Section: Discussionmentioning
confidence: 97%